Polemik Kekerasan Dengan Legitimasi Bina Tradisi (Bintra) Dalam Pembentukan Mental Bintara Remaja: Tinjauan Terhadap Peraturan Kapolri Nomor 8 Tahun 2009 Tentang Implementasi Prinsip Dan Standar Hak Asasi Manusia - I Made Cipta Haryasa; I Gusti Ngurah Anom (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2026)
This study examines the controversy surrounding violence in Bina Tradisi (Bintra) in the mental formation of Junior Police Officers (Bintara Remaja) within the Indonesian National Police, based on Regulation of the Chief of Police Number 8 of 2009 concerning Human Rights. The main issue lies in the vagueness of law, not a legal vacuum, as the prohibition of violence already exists but lacks clear operational guidelines. This research applies a normative legal method using statutory, conceptual, and case approaches. The findings reveal that violent practices contradict the principles of legality, proportionality, and human dignity. Therefore, regulatory reformulation, strengthened oversight, and consistent sanction enforcement are necessary to ensure professional and humanistic training.